No Influence of Emotional Faces or Autistic Traits on Gaze-Cueing in General Population - Uono, Shota; Egashira, Yuka; Hayashi, Sayuri; Takada, Miki; Ukezono, Masatoshi; Okada, Takashi (Frontiers in Psychology, 2022)
The present study addressed the controversial issue of whether autistic traits in the general population are associated with the automatic and fundamental aspects of joint attention through eye gaze. Specifically, we examined whether the degree of autistic traits is associated with the magnitude of reflexive attention orienting in the direction of another’s eye gaze embedded in neutral and emotional (angry, fearful, and happy) faces. The cue stimuli changed gaze direction and facial expressions simultaneously. Participants were asked to detect a target that appeared at the left or right of the cue stimuli. The results revealed a robust gaze-cueing effect, such that the reaction time to the target was shorter under the gaze-at-target condition than under the non-gaze-at-target condition. However, emotional expressions did not modulate the gaze-cueing effect. Furthermore, individual differences in autistic traits and emotional characteristics (social anxiety, alexithymia, and emotional disturbances) did not influence the magnitude of the gaze-cueing effect. Although the ability to orient attention in the direction of another’s gaze is a fundamental function of social development, the gaze-cueing effect measured in a controlled experiment might not be an elaborate representation of the current social cognitive function, at least in typically developing individuals.